Continuation theory for general contractions in gauge spaces. Issue 3 (26th August 2004) - Chiş, Adela; Precup, Radu
Abstract : A continuation principle of Leray-Schauder type is presented for contractions with respect to a gauge structure depending on the homotopy parameter. The result involves the most general notion of a contractive map on a gauge space and in particular yields homotopy invariance results for several types of generalized contractions.